14-3-3s are DNA-replication proteins. (August 2002) - Zannis-Hadjopoulos, M.; Novac, O.; Alvarez, D.; Price, G. B.
Abstract : 14-3-3 proteins are conserved multifunctional molecules, involved in many biological processes. Several 14-3-3 isoforms were recently shown to be cruciform DNA-binding proteins, which is a new activity ascribed to the 14-3-3 family. As cruciform-binding proteins, 14-3-3 proteins are putatively involved in the regulation of DNA replication. Inverted repeat sequences that are able to extrude into cruciform structures are a common feature of replication origins in both prokaryotes and eukaryotes. The involvement of cruciform structures in the initiation of DNA replication has been demonstrated. A leading model of 14-3-3 function proposes that they facilitate critical protein-protein interactions, thus serving as a central component of a wide variety of cellular processes.